Judicial Reasoning in Sidoarjo District Court Decision No. 199/Pid.Sus/2023: Corporate Criminal Liability in Environmental Crimes - Samsul Hadi; Dudik Djaja Sidarta; Renda Aranggraeni; M. Yustino Aribawa (PT. Banjarese Pacific Indonesia, 2025)
This study analyzes the judicial reasoning behind Putusan Pengadilan Negeri Sidoarjo No. 199/Pid.Sus/2023/PN Sda, a landmark decision involving corporate criminal liability for environmental violations in Indonesia. The case centers on PT Surya Prima Semesta’s illegal disposal of hazardous waste (fly ash and bottom ash) without an environmental permit, resulting in the prosecution of its corporate director. Employing a normative juridical method, the research examines the court’s application of doctrines such as strict liability and identification theory within the framework of Law No. 32 of 2009 on Environmental Protection and Management. The findings show that the court adopted a formalistic, text-based legal reasoning model, treating permit violations as inherently punishable acts regardless of actual environmental harm. While the decision reinforces regulatory compliance and affirms corporate culpability, it lacks engagement with broader organizational responsibility and foundational environmental law principles like the precautionary principle and sustainability. This study argues for a more integrated doctrinal approach one that balances rule-based logic with value-oriented reasoning to enhance legal consistency, advance environmental justice, and align Indonesia’s corporate accountability framework with international standards.